Conceptual Metaphors in Mylo Xyloto Album by Coldplay - Selvia Neilil Kamaliah (Universitas Pendidikan Indonesia (UPI), 2013)
This study investigates Conceptual Metaphor (CM) used in song lyrics. The study uses the song lyrics of Coldplay’s album entitled Mylo Xyloto as data. In analyzing the data, the qualitative method especially a case study is used. Furthermore, the data are analyzed using the framework of the Conceptual Metaphor Theory (CMT) (Lakoff and Johnson, 1980a, 1980b; Kovesces, 2002, 2010). The study found that the dominant conceptual metaphors used are about life, love, changes and conditions, namely LIFE IS JOURNEY, CHANGES ARE MOVEMENT, PURPOSES ARE DESTINATION, LOVE IS A UNITY, LOVE IS WAR, LOVE IS STRUGGLE, STATES ARE LOCATIONS, and LESS IS DOWN. Keywords: Conceptual Metaphor Theory (CMT), song lyrics, Coldplay